Running economy benefits of advanced footwear technologies remain over a prolonged run in highly trained distance runners - a randomized crossover trial - Schwalm, L. C.; Fohrmann, D.; Schaffarczyk, M.; Herrmann, A.; Gronwald, T.; Hollander, K. (Medicine & Science in Sports & Exercise, 2025)
Purpose Running economy (RE) improvements in advanced footwear technologies (AFTs) have been investigated during short running bouts, whereas performance-enhancing effects may be greater over longer distances. Therefore, the aim was to compare RE and biomechanics during a 90-min run between AFTs and traditional shoes in highly trained distance runners.